PERANAN BIDAN DESA DALAM MENANGANI DAN MERUJUK KASUS BAYI BARU LAHIR ASFIKSIA DI KABUPATEN CIREBON - Umniyati, Helwiah (Lembaga Penelitian Universitas YARSI, 2007)
Each year 3 million newborns die during the first seven days of life, accounting for 75% of all neonatal deaths. At least 1 million babies die during their first 24 hours of life. Three major causes of neonatal death are infections (pneumonia, diarrhea, and tetanus) 36%, preterm birth 28% and asphyxia 23%. Causes of death vary between the early and late neonatal periods, with deaths caused by preterm birth, asphyxia and congenital defects occur predominantly during the frst week of life and infection is the major cause of neonatal deaths thereafter. In Indonesia based on 2001 Household Health Survey (SKRT 2001) neonatal death caused by asphyxia was 27% which was the second cause of neonatal death after low birth weight. The objective of this study was to learn the role of midwives in handling and referring birth asphyxia in Cirebon District by using qualitative method. The result showed that many people living in villages in Cirebon district did not understand the causes of asphyxia. They thought that babies could not cry because of bad spirit or devil. The midewives were capable of handling the asphyxia babies according to their knowledges obtained from training about asphyxia management. Sometimes however, the midwives encountered some constrains in practice such as low birth weight babies (only 1,4 Kg) and oversize concave cover for resuscitation. Other limiting factors occurred when the midwives would like to refer the babies to the hospital. The families might refuse with some reasons such as, no trust in the medical staff, shortage of money or difficulty in finding transportation. Lack of incubator in the hospital was also another obstacle.